Healthcare accessibility to rabies post-exposure prophylaxis in rural Kenya: implications for vaccine placement and travel time - Mutunga, Mumbua; Nyamai, Mutono; Mazeri, Stella; Ksee, Daniel; Maritim, Marybeth; Mbaire, Chuchu; Hampson, Katie; Thumbi, S. M. (Frontiers in Microbiology, 2026)
BackgroundRabid animal bites are a medical emergency, requiring immediate post-exposure prophylaxis (PEP) to prevent human deaths. This study modeled geographical accessibility to health facilities stocking rabies vaccines and assessed the impact of optimizing vaccine placement within a rural Kenyan healthcare network.MethodsWe used geocoordinates of Kenyan health facilities from an open-access inventory and identified those stocking PEP in Makueni County. Using population distribution data and a travel time friction surface, we estimated travel times to all health facilities, including those stocking PEP. We assessed the proportion of the population within 30 min, 1, 1.5, 2, and >2 h of these facilities. We further used dog-bite data from contact-tracing studies (2017–2021) to estimate the shortest distance and travel time for patients accessing PEP.ResultsTwo-thirds (66.6%) of the population lived within a 30-min walk to any health facility, but only 7.4% had similar access to a PEP facility. Using the non-motorized travel scenario, 66.6, 29.4, 3.5, 0.3, and 0.2% of the population were within 30 min, 1 h, 1.5 h, 2 h, and more than 2 h of walking time, respectively, to any health facility. Among 931 bite patients identified through contact tracing, 376 (40.4%) could reach any health facility within 10 min, while only 289 (35.4%) had similar access to a PEP facility. Additionally, 27 (2.9%) required over 60 min to reach any health facility, while 26 (3.2%) needed over 60 min specifically to access PEP. When considering motorized travel, the entire population was within 30 min of both any facility and a PEP facility.ConclusionOur findings demonstrate that increased geographic distance and longer travel times to health facilities substantially reduce accessibility to rabies PEP, particularly in rural settings where reliance on non-motorized travel is common. To our knowledge, this is the first study to provide quantitative, county-specific estimates of travel time impacts on PEP access in rural Kenya, filling a critical evidence gap for planning PEP distribution under Kenya’s Stepwise Approach to Rabies Elimination (SARE). Optimizing the placement of PEP within existing healthcare networks can increase the proportion of the population able to reach services within recommended time thresholds. Expanding vaccine availability at strategically located facilities would therefore improve timely PEP to bite victims and support efforts to prevent human rabies deaths. These results highlight the importance of incorporating geographic accessibility analyses into planning for rabies elimination programs.